Students' Mathematical Critical Thinking Reviewed from Gregorc's Thinking Style in Flipped Classroom Learning Assisted by Google Site - Ramadhani, Dinda Puspa; Kurniasih, Ary Woro (Unnes Journal of Mathematics Education, 2025)
Mathematical critical thinking is essential, especially for students. This study aims to describe students' mathematical critical thinking according to Facione, as reviewed from Gregorc's thinking style in Flipped Classroom learning assisted by Google Site. The research method used is qualitative descriptive. The subjects of this study were students in class X-D SMA Negeri 1 Padamara in Purbalingga who were selected using purposive sampling techniques, namely 2 students from each type of Gregorian thinking style, namely 2 Concrete Sequential (CS) students, 2 Abstract Sequential (AS) students, 2 Abstract Random (AR) students, and 2 Concrete Random (CR) students. The data collection techniques in this study are tests, questionnaires, interviews, observations, and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing. The results show that in Flipped Classroom learning assisted by Google Site, students' mathematical critical thinking varies based on Gregorc's thinking style. Concrete Sequential (CS) students can do interpretation and inference, not optimal in analysis and evaluation, and need to be explored in explanation. Abstract Sequential (AS) students can do interpretation, evaluation, inference, and explanation well, but they are not optimal in analysis. Abstract Random (AR) students can do interpretation and inference, but not optimally in analysis, evaluation, and explanation. Meanwhile, Concrete Random (CR) students can do interpretation and inference, which is not optimal in analysis, and need to be explored in evaluation and explanation. Flipped Classroom learning assisted by Google Site is expected to be applied in the classroom to help stimulate students' mathematical critical thinking.